Combined densification and pulsed electric field treatment for selective polyphenols recovery from fermented grape pomace. (May 2015) - Brianceau, Sylène; Turk, Mohammad; Vitrac, Xavier; Vorobiev, Eugène
Abstract: The aim of this study is to assess a new process for the valorization of fermented grape pomace using pulsed electric fields (PEF). The combination of densification and PEF treatment was applied on grape pomace of low relative humidity, without any addition of conductive liquid. The kinetics of extraction and the composition of polyphenols were evaluated throughout the subsequent hydro-alcoholic extraction at different temperatures. Optimal parameters of PEF treatment (field strength E = 1.2 kV·cm − 1 ; energy input W = 18 kJ·kg − 1 ; density ρ = 1.0 g·cm − 3 ) increased the content of total polyphenols regardless of the temperature of extraction. The ratio of total anthocyanins to total flavan-3-ols at 20 °C was equal to 7.1 and 9.0 for control and PEF treated modalities, respectively. These results demonstrate the selective nature of PEF treatment in anthocyanin extraction, and thus reveal new possibilities to produce extracts with different biochemical compositions. Industrial relevance: This study examines the feasibility of densification combined with PEF pre-treatment of relatively low humidity grape pomace for the enhancement of bioactive compounds extraction. The concentration of total phenolic compounds obtained after PEF treatment showed that the use of this technique is relevant for an industrial use, since solvent amount and extraction time can be reduced. Moreover, the selective nature of PEF opens the opportunity to produce extracts of different biochemical compositions. This process is an alternative to conventional pre-treatments of raw material (e.g. dehydration and grinding), which have impacts on product quality and are more energy consuming. Highlights: PEF treatment is applied to fermented grape pomace of low relative humidity. PEF process is efficient in recovering polyphenols without addition of liquid. Densification should be considered as an important parameter for PEF efficiency. The effects of electric field strength, density and temperature are studied. PEF is a selective process for recovery of anthocyanins at low energy costs.